THE EFFECT OF FINANCIAL LITERACY ON RISKY CREDIT BEHAVIOR IN THE USE OF GOPAYLATER WITH FINANCIAL SELF-EFFICACY AS A MEDIATING VARIABLE - Tiffany; Nor Norisanti; Sopyan Saori (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
Technological advances have encouraged people to adopt an instant lifestyle, including in financial matters. One widely used innovation is the Buy Now Pay Later (BNPL) service, such as GoPayLater. While offering convenience, the use of this service carries the risk of fostering risky credit behavior, especially if it is not accompanied by adequate financial literacy and financial self efficacy. This study aims to investigate the influence of Financial Literacy on Risky Credit Behavior and to test the mediating role of financial self-efficacy. This study employs a quantitative approach using an associative causal method. The sampling technique in this study uses purposive sampling of 155 GoPayLater users who follow the @discountfess account on the X app. The data analysis technique used in this study is Structural Equation Modeling (SEM) using Partial Least Square (PLS). The results of the study indicate that Financial Literacy has a negative and significant effect on Risky Credit Behavior, as well as a positive and significant effect on Financial Self-Efficacy. Financial Self-Efficacy also has a positive and significant effect on Risky Credit Behavior and is proven to effectively mediate the relationship between financial literacy and risky credit behavior.